Analisis CSR Perusahaan Farmasi Tahun 2020 dan 2021 - Asyayidah, Khoirunnisak Amalia; Agustina, Rachma (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Social responsibility or also known as Corporate Social Responsibility (CSR) exists because of the need for a business entity to pay attention to the condition of the surrounding social environment. Business entities are not only concerned with achieving profit or profits but must also pay attention to social and environmental aspects as well. This study uses a qualitative approach research method. PT. Kimia Farma and PT. Kalbe Farma has been responsible for its social responsibility. Disclosure of social responsibility at PT. Kimia Farma disclosed in its sustainability report and annual report clearly the realization of the Corporate Social Responsibility budget that was made to fund Corporate Social Responsibility programs in contrast to PT. Kalbe Farma which only disclosed the amount of Corporate Social Responsibility funds. PT. Kimia Farma and PT. Kalbe Farma does not classify Corporate Social Responsibility expense accounts in detail in the income statement.